Efficient trade-offs as explanations in functional linguistics: some problems and an alternative proposal - Levshina, Natalia (Revista da ABRALIN, 2020)
The notion of efficient trade-offs is frequently used in functional linguistics in order to explain language use and structure. In this paper I argue that this notion is more confusing than enlightening. Not every negative correlation between parameters represents a real trade-off. Moreover, trade-offs are usually reported between pairs of variables, without taking into account the role of other factors. These and other theoretical issues are illustrated in a case study of linguistic cues used in expressing “who did what to whom”: case marking, rigid word order and medial verb position. The data are taken from the Universal Dependencies corpora in 30 languages and annotated corpora of online news from the Leipzig Corpora collection. We find that not all cues are correlated negatively, which questions the assumption of language as a zero-sum game. Moreover, the correlations between pairs of variables change when we incorporate the third variable. Finally, the relationships between the variables are not always bidirectional. The study also presents a causal model, which can serve as a more appropriate alternative to trade-offs.